STUDI ETNOBOTANI PEMANFAATAN TUMBUHAN DURIAN (Durio spp) di DESA LABIAN IRA’ANG KECAMATAN BATANG LUPAR KABUPATEN KAPUAS HULU - Suprianto, Antonius; Diba, farah; Prayogo, Hari (Universitas Tanjungpura, 2018)
Ethnobotany is a study of the utilization of plants used by a particular ethnic or tribe to meet the needs of clothing, food, boards, and drugs. Durian (Durio spp) dubbed as the King of Fruit is one of the popular fruit in Indonesia. This study aims to study the ethnobotany and utilization of durian plants ranging from roots, stems, skins, flowers, and fruit in Labian Iraâ€™ang village, Batang Lupar sub district, Kapuas Hulu regency. The method used is the snowball sampling. Through snowball sampling technique the samples were selected on the basis of person to person recommendations according to the study to be interviewed. The results showed that there are two species of durian in Labian Ira'ang village, Batang Lupar sub-district, Kapuas Hulu regency. The species of durian consist of Durio kutejensis and Durio zibethinus, with 8 local names: Durian pepakan, Durian kuraras, Durian burawing, Durian lelek , Durian malele, Durian besusuk, Durian kaban and Durian tempurung. Â There are others type of durian fruit and the local community called local durian. The name of local durian was done with the condition of the place where it grows and who planted it. The parts used by the community include roots, stems, bark, flowers, leaves, fruit, fruit peel and seeds. Durian plants are not only utilized for one or two uses, but many are used with various uses. In addition, durian plants also have a view that is part of the belief by the local community by utilizing the flowers as an abundant of rice producer.Keywords: Durian, Durio zibethinus, Durio kutejensis, Etnobotani, Tembawang